Fixed or open-ended? Labor contract and productivity in the Colombian manufacturing sector - Francesca Castellani; Giulia Lotti; Nataly Obando (Journal of Applied Economics, 2020)
Using the Colombian Annual Manufacturing Survey (AMS) between 2000 and 2014, this paper investigates the effect of labor contract modalities on firm productivity within the industrial sector through a structural model. We find that the elasticity of revenue with respect to temporary workers is often lower than that with respect to permanent workers, but not in small firms, where some forms of flexibility might lead to productivity gains.
Keywords: 330; firms' TFP; Labor contracts; skilled workers; temporary workers